Shift Sector Analysis of Economy in Mamminasata Region - Ratu Pratiwi, Fadhila; Khusaini, Moh; Susilo, Susilo (Institute of Research and Community Service, University of Brawijaya, 2016)
Mamminasata region which is located in South Sulawesi Province consists of Makassar City, Maros District, Gowa District and Takalar District. The districts have sourced leading sectors which can contribute to each area. This study aims to determine whether the leading sector have a shift sector in the Mamminasata region by using shift share tools analysis to find competitive sector. This study uses secondary GDP (Gross Domestic Product) data from Central Bureau of Statistics South Sulawesi Province in 2006 and 2013. Based on the results, Makassar City does not have a shift sector and the trade sector is not a competitive sector. Maros District has a shift from agriculture to industry but this sector is a competitive sector. Gowa District does not have a shift sector in agriculture sector and this sector is not competitive sector. It differs from Takalar District which does not have a shift sector in agriculture sector and fishery sector is competitive.